Revisiting innovation typology: A systemic approach - Louis Knuepling; Colin Wessendorf; Stefano Basilico (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2022)
Innovation studies use labels such as radical or disruptive to qualify innovation according to different concepts. Within the literature, these labels are frequently used interchangeably due to overlaps in their characteristics. These various definitions present challenges when the labels are operationalized in empirical studies. Based on a quantitative analysis of the most common innovation labels' definitions in 532 scientific papers, we find that novelty and impact, predominantly used for empirical operationalization, differentiate only between ordinary and more exceptional innovations. Based on our findings, a differentiation between the impact's target and the consideration of positive versus negative effects enables better distinction between labels for more "exceptional" innovations. We extend the existing literature and enable a more precise definition of (single) innovations by providing a novel, more nuanced description of innovations' different characteristics and a further distinction of their effects. Thereby, the relevant decisive aspects will be communicated more accurately.
Keywords: O31; O32; O33; 330; radical; incremental; disruptive; breakthrough; innovation typology